Penguatan elemen profil pelajar pancasila melalui kegiatan kampus mengajar bagi peserta didik sekolah dasar - Dahlia Sidabutar (COLLASE (Creative of Learning Students Elementary Education), 2023)
Forming an alpha generation by gaining knowledge through the scope of the school has become the responsibility of all parties involved in driving the advancement of education in Indonesia. The era of technological sophistication makes it easier for every individual activity and even expands access to exploring the progress of other countries. In Indonesia itself, they feel comfortable from the effects of digitalization, but at the same time, the influence of globalization as an influence from outside culture is not all in accordance with the values of Pancasila in Indonesia. With these problems, it is feared that the Indonesian people will forget their own national identity which upholds the values of Pancasila as a form of good citizen. This research aims to cultivate the character of basic students according to the profile of Pancasila students through one of the prestigious MBKM programs, namely teaching campus activities. Realizing the values of the Pancasila student profile should be strengthened for students because it will be a benchmark for the success of a nation in the future. The method in this general research is descriptive qualitative. The research location is in one of the elementary schools in Cibeureum District, Tasikmalaya City. The sample of this research included school principals, teachers, five students, six students. Data collection techniques by way of observation, interviews and documentation. Sources of research data are also strengthened from relevant journals. Based on the results of research on strengthening the values of the Pancasila Student Profile through teaching campus activities, it shows that various types of teaching campus activities can shape the strengthening of the Pancasila student profile in elementary schools. With innovations in teaching campus activities in collaboration with teachers through routines and habits, the values of the elements of the Pancasila student profile can be instilled.